2021
DOI: 10.1111/ejn.15103
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characteristics of subthalamic nucleus local field potentials in Parkinson's disease: Phenotype and movement matter

Abstract: Parkinson's disease (PD) is clinically heterogeneous across patients and may be classified in three motor phenotypes: tremor dominant (TD), postural instability and gait disorder (PIGD), and undetermined. Despite the significant clinical characterization of motor phenotypes, little is known about how electrophysiological data, particularly subthalamic nucleus local field potentials (STN‐LFP), differ between TD and PIGD patients. This is relevant since increased STN‐LFP bandpower at α–β range (8–35 Hz) is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
1
14
0
Order By: Relevance
“…The differences observed in our study between AR and TD may reflect differences in these STN-cortical interactions. This is further supported by the previous work demonstrating greater high beta power in freezers compared to non-freezers ( Toledo et al, 2014 ) and tremor-dominant vs. akinetic-rigid ( Godinho et al, 2021 ) at rest. Together, these results point to a pathological low beta oscillation that is consistent across phenotypes and then a potentially separate high beta oscillation that may be more specific to akinetic-rigid symptoms regardless of task.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The differences observed in our study between AR and TD may reflect differences in these STN-cortical interactions. This is further supported by the previous work demonstrating greater high beta power in freezers compared to non-freezers ( Toledo et al, 2014 ) and tremor-dominant vs. akinetic-rigid ( Godinho et al, 2021 ) at rest. Together, these results point to a pathological low beta oscillation that is consistent across phenotypes and then a potentially separate high beta oscillation that may be more specific to akinetic-rigid symptoms regardless of task.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies that have evaluated phenotype differences primarily focused on high (20–35 Hz) and low (10–20 Hz) beta band power in the operating room or perioperative state (i.e., the week after implantation). Differences in high beta band power were demonstrated between tremor-dominant (TD) and akinetic-rigid (AR) phenotypes at rest, but not during movement in an elbow-flexion task in the operating room ( Godinho et al, 2021 ). Furthermore, within band differences between rest and movement were observed for each phenotype (low beta for tremor-dominant and high beta for akinetic-rigid).…”
Section: Introductionmentioning
confidence: 99%
“…tremor dominant PD vs. postural instability gait disorder phenotypes. Godinho et al (2021) found that supervised learning algorithms aimed at discriminating PD phenotypes based on STN-LFP band power features were most accurate when tremor dominant and postural instability gait disorder movement-induced desynchronization ranges were considered (41). Future studies can employ such algorithms and include genotype to improve phenotypic classification using physiologic signals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have evaluated phenotype differences primarily focused on high and low beta band power in the operating room or perioperative state (i.e., the week after implantation). Differences in high beta band power were demonstrated between tremordominant and akinetic-rigid subtypes at rest, but not during movement in an elbowflexion task in the operating room (Godinho et al, 2021). Furthermore, within band differences between rest and movement were observed for each subtype (low beta for tremor dominant, high beta for akinetic rigid).…”
Section: Introductionmentioning
confidence: 83%